Bristol's smart city agenda: vision, strategy, challenges and implementation. Issue 4 (13th November 2020) - Lockwood, Freyja
Abstract : This case study explores Bristol's goal to create a smart city, anchored by a 30‐year city vision and the vital role digital connectivity and smart city technologies play. It describes Bristol's 2050 One City Plan, where city partners are collaboratively shaping the city through place‐based leadership, community involvement and co‐production, and Bristol City Council's complementary smart city strategy – Connecting Bristol. This digital agenda supports by developing the 'foundations' required to become a data‐enabled city with world‐class connectivity and inclusive public services; elements which enable many One City goals. It examines the importance of a challenge‐led, people‐focused approach with responsible innovation practices that ensure digital initiatives align with the One City Plan's equitable goals and values. Implementation strategies, including an 'innovation ambition' matrix used to manage a portfolio of smart city initiatives, and challenges are described along with the need for inclusive infrastructure and ethical data practices. The emerging role for local government in shaping a trusted smart city is explored. This study ends by discussing Covid‐19 and economic recovery, in response to which the Council seeks to become a more agile, streamlined organisation, and concludes by highlighting the need to keep people at the heart of 'smart' city development.